Review of Previous Research Works Done on Tamak Shwasa Conducted Across India and Role of Different Treatment Modalities in Tamak Shwasa - Rawat, Vandana; Tripathi, Arun Kumar; Tiwari, P R (International Research Journal of Ayurveda & Yoga, 2022)
At present era, many chronic recurrent airway disorders are increasingly seen all over the global population. Tamak Shwasa is one of such disorder described in Ayurveda. It is one of the variety among five types of Shwasa roga characterized by prolonged expiration, wheeze, dyspnoea of exceedingly deep velocity, which is immensely injurious to life. In modern science, it can be correlated with bronchial asthma. According to Ayurveda Tamak shwasa is a Yapya vyadhi. It is not serious as Maha, Urdhva and Chhinna shwasa but it is a very troublesome disease and long lasting with frequent episodes (attacks) difficult to bring under control unless quick and prompt treatment is not provided. Shodhana and Shaman chikitsa are the important line of treatment described in Ayurvedic classics. Shodhana karma is studied to be a necessary prerequisite in managing Shwasa roga, particularly in patients with sufficient strength, because the disease is manifested by the aggravated Prana vayu and by the obstruction of Kapha. Similary there are lots of herbal drugs and rasa preparation having Vatakaphashamak, Ushna, Vatanulomana, Shwasahar and Kasahara properties which seems to be very effective in the treatment of Tamak shwasa. So there are many research studies were done by various previous scholars on Shodhana karma, rasa preparation and herbal drugs to analyse their efficacy and effectiveness on the disease Tamak shwasa.